Recent treatment guidelines for managing adult patients with sickle cell disease: challenges in access to care, social issues, and adherence. Issue 6 (2nd June 2016) - Adams-Graves, Patricia; Bronte-Jordan, Lanetta
ABSTRACT: Introduction: Advances in research, medical care, and public health practice have led to individuals with sickle cell disease (SCD) living into adulthood. However, premature mortality persists in youth and young adults with SCD, and adults with SCD are subjected to increased disease burden, organ damage, pain, and disruptions in family and work life. Areas covered: These issues have led to inappropriate utilization of hospital resources, significantly increasing costs related to prolonged inpatient stays, high readmission rates, and increased emergency room visits. Expert commentary: Steps are being taken to address these challenges to improve care, including development of evidence-based guidelines targeted to primary care providers, innovative care models, and programs to prepare adolescents for transition to adult care. Previous and current guidelines, as well as health-care policies and practices, for treatment of adults with SCD are reviewed.